Singular integration with applications to boundary value problems - Kaye, Adelina E. (Kansas State University, 2016)
This report explores singular integration, both real and complex, focusing on the the Cauchy type integral, culminating in the proof of generalized Sokhotski-Plemelj formulae and the applications of such to a Riemann-Hilbert problem.
Keywords: Boundary Value Problem; Singular Integration; Sokhotski; Plemelj; Riemann-Hilbert; Cauchy type integral